Quality assurance in universities in the muslim world: obstacles and solutions - Salleh, Mohamad Johdi; Kayode, Bakare Kazem (2009)
Human beings are creatures from unknown to known. The struggle of human being on earth is to gain freedom back to his initial abode. The intellectual and spiritual endowment that was given to man in creation is not only to worship (Allah) as command, but it’s also serves as a divine gift from the creator; to enable him develop himself in a balance mode. This intellectual acumen given to man by Allah is to make him respond adequately to his environmental challenges by being creative in response to his need at a time. The creative tendencies endowed to man made it possible for him to discover and develop ideas that are capable of satisfying the needs of the entire human race. Today, these creative abilities of man have manifested in different forms among them are: product design, handicraft, Auto-mobile assembly-line, Education, culture and moral. These endowed resources of man; which enables him to generate idea, synthesis product, acquire and disseminate useful information have attracted different nomenclature which varies over the years. It was initially tagged labor, later to manpower, to human resources and the most resent name is human capital. Having identify these potentials in man, and its ability to transform concrete resources into a profitable use, maintaining these qualities in human being become a yardstick in determining “quality”. Quality assurance/Total Quality Management, Quality product, Quality material, Quality service, Quality Education, Quality Health e.t.c. are variations of quality, which are largely premised on human potentials and creativity. This paper shall therefore provide a summary of status of quality of education in universities in Muslim world and critically analyses the issue of quality with the backdrop of problems, constraints, and conflicts. Towards the end, suggests appropriate solutions with several alternatives, to improve quality, discussing also their feasibility. The general objective is to develop strategies for improving quality assurance in the Universities in the Muslim word.